KAPASITAS AEROBIK DAN ANAEROBIK PADA ANAK LAKI-LAKI DAN PEREMPUAN USIA DINI DITINJAU DARI KETINGGIAN WILAYAH DI PROVINSI JAWA TENGAH - Satrio Sakti Rumpoko; Sunjoyo Sunjoyo (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2020)
The purpose of this research is (1) to know the difference in aerobic and anaerobic capacity between children who are born and living on high ground with children born and living in Lowlands, (2) to find out the difference in aerobic and anaerobic capacity between boys, with girls, (3) and to know the effect of interactions between the region and gender-based aerobic capacity. The research was carried out by the post-facto ex method with a 2x2 factorial design. Aerobic capacity data is obtained from the Multi-Stage Fitness Test (MFST/Beep Test), while anaerobic capacity data obtained from Test 50 yard.Â  Data analysis techniques of aerobic capacity and anaerobic using ANAVA 2 x 2 variance analysis with significance a = 0.05.Â  The results of the study can be described as follows: (1) There are significant differences between male and female gender in the aerobic and anaerobic observation that male gender tends to be better than women (2) There are significant differences between those living on the plains. High and lowland on aerobic and anaerobic observation i.e. those living on a plateau tend to be better than those living in lowland (3) there is interaction between gender and location on anaerobic observation i.e. women living in the lowlands tend to have decreased more anaerobic ability than decreased anaerobic ability in males (4) No sex interactions and locations on aerobic observation.